The Relationship between Serum Markers of Collagen Turnover and Cardiovascular Outcome in the Elderly: The Cardiovascular Health Study - Barasch, Eddy (2011)
BACKGROUND: The deposition of collagen fibrils in the myocardial extracellular matrix increases with age and plays a key role in the pathophysiology of heart failure (HF). We sought to determine the predictive value of serum markers of collagen turnover for incident HF and cardiovascular (CV) morbidity, mortality and all-cause mortality in elderly individuals. METHODS AND RESULTS: In 880 participants in the Cardiovascular Health Study (mean age 77 ± 6 yrs, 48% female), serum levels of carboxyl-terminal peptide of procollagen type I (PIP), carboxyl-terminal telopeptide of collagen type I (CITP), and amino-terminal peptide of procollagen type III (PIIINP) were measured in 4 groups: HF with reduced ejection fraction (HFREF; n=146, EF < 55%); HF with preserved EF (HFPEF; n=175, EF ≥ 55%), controls with CV risk factors but not HF (CVD; n = 280) and healthy controls free of CV disease (n=279). Relationships between these serum markers and outcome at follow-up of 12 ± 4 years (range, 3-17 years) was determined in six models including those adjusted for conventional risk factors, renal function, NT-proBNP and agents which interfere with collagen synthesis. For the entire cohort, in unadjusted and adjusted models, both PIIINP and CITP were associated with myocardial infarction, incident HF, hospitalization for HF, cardiovascular and all-cause mortality. In healthy controls, CITP and PIIINP were associated with all-cause death. In controls with risk factors, CITP was associated with incident HF, and in participants with HFPEF, CITP was associated with hospitalization for HF. No collagen biomarker was associated with outcome in participants with HFREF, and PIP was not associated with outcome in the cohort or its subgroups. CONCLUSIONS: In both healthy and elderly individuals with CV disease at risk of developing HF, CITP and PIIINP are significantly associated with multiple adverse cardiac outcomes including myocardial infarction, HF and death. CLINICAL TRIAL REGISTRATION: URL: http://www.chs-nhlbi.org. Unique Identifier: NCT00005133.